Growth of Antarctic plants Colobanthus quitensis and Warnstorfia fontinaliopsis in the presence of Cr (VI) in vitro - N. A. Matvieieva; V. P. Dupliy (Ukrainian Antarctic Journal, 2010)
Influense of K2CrO4 on the growth of two Antarctic plants – Colobanthus guitensis (Kunth) K2CrO4 Bartl and Warnstorfia fontinaliopsis (Müll.Hal.) Ochyra in vitro culture has been studied. Under the Cr(VI) treatment at concentration from 10 to 100 mg/l the shoot length augmentation of W. fontinaliopsis did not differ from the augmentation in control. The increase in Cr(VI) concentration in a nutrient medium to 150 mg/l led to inhibition of growth and essential reduction of a biomass augmentation both vascular plant and moss. There were statistically authentic distinctions in relative callus weight augmentation of C. guitensis and N. tabacum on the medium supplemented with 10 or 100 mg/l of Cr(VI) respectively. So C. guitensis is more sensitive to toxic metal than N. tabacum. Under the150 mg/l Cr(VI) the C. guitensis and N. tabacum relative callus weight augmentations were respectively in 56,4 and 20,5 times less than in control (0,09 and 0,33 g per 1 g initial weight).